8 years study of pharyngocutaneous fistula following total laryngectomy at C. H. Baragwanath Hospital - Sabri, Issam Fetouri (My University, 2010)
Introduction The bulk of the surgical literature about laryngeal cancer is concerned with cure rates or five-year survival rates. While this is important, the five year survival rate is only one measure of success of laryngeal cancer surgery. Whereas, postoperative morbidity and mortality are also very important. Pharyngocutaneous fistula (PCF) is the most frequent complication in the early post operative period after total laryngectomy. It creates a communication between the pharynx and the cervical skin or less frequently with the stoma of the tracheostomy. The pharyngeal contents, usually saliva, flow through the fistula emerging from the cutaneous orifice. This study aims to determine the incidence and the predisposing factors for the development of pharyngocutaneous fistula (PCF); and to review the management and outcome of such cases following total laryngectomy at Ear, Nose and Throat (ENT) department, Chris Hani Baragwanath Hospital. Patients and methods This is a retrospective study. The medical records of 30 patients who underwent total laryngectomy surgery for squamous cell carcinoma of the larynx with no local neck metastases between June 2000 and May 2008 were assessed. iii All patients had similar (standard) preoperative and post operative care. I studied a number of factors that could influence pharyngocutaneous fistula formation such as age, smoking habit, alcohol consumption, tumour stage, preoperative tracheostomy, preoperative hemoglobin and associated systemic diseases (gastroesophageal reflux, chronic obstructive pulmonary disease, systemic high blood pressure and diabetes mellitus) Results Pharyngocutaneous fistula appeared in 20% (6/30 patients). Spontaneous closure with local wound care was noted in 5 patients (83.3%), whereas a surgical closure was necessary in one patient . Conclusion The results of our study concluded that pharyngocutaneous fistula remains a troublesome complication of the early post-operative period after total laryngectomy. There are many conflicting reports in the literature concerning the pharyngoctaneuos fistula predisposing factors, but our study data (table 1 page 22) of age, smoking habit, alcohol consumption, tumor stage, preoperative tracheostomy, preoperative hemoglobin and associated systemic diseases( gastroesophageal reflux, chronic pulmonary obstructive disease, systemic high blood pressure and diabetes mellitus) did not show any significant value. Our experience confirmed that most pharyngocutaneous fistulas can be successfully treated conservatively.
MMed (Otorhinolargngology). Faculty of Health Sciences, University of the Witwatersrand
Keywords: laryngectomy complications; pharyngocutaneous fistula